2012
DOI: 10.1007/s10857-012-9203-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the development of prospective mathematics teachers’ pedagogical content knowledge of generalising number patterns through school practicum

Abstract: The purpose of this study is to investigate the development of three prospective elementary mathematics teachers' pedagogical content knowledge (PCK) of number patterns with its two components: (1) knowledge of students' understanding and difficulties and (2) knowledge of topic-specific strategies and representations. For our investigation, we use Radford's (ZDM Math Educ 40:83-96, 2008) framework called 'architecture of algebraic pattern generalisation' to redefine these two components of PCK in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Studies 8,25,28,30,31,33, and 51, which had examined the development of PCK, stated that courses whose content was designed to reinforce teacher candidates had a positive effect on their development of PCK through reinforcement. Study 9 found that classroom teachers' PCK progressively improved during their university education.…”
Section: Main Results Obtained By Studies Conducted To Determine Pck mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies 8,25,28,30,31,33, and 51, which had examined the development of PCK, stated that courses whose content was designed to reinforce teacher candidates had a positive effect on their development of PCK through reinforcement. Study 9 found that classroom teachers' PCK progressively improved during their university education.…”
Section: Main Results Obtained By Studies Conducted To Determine Pck mentioning
confidence: 99%
“…As can be seen in Table 7, the interview was the most frequently used data collection tool in the studies. The interviews were generally conducted on scenarios that reflected the way students think (1, 3, 4, 9, 10, 12, 13, 19, 20, 27, 29, 32, 38, 53), course schedule as prepared by the participants (5,6,7,8,9,21,26,28), or teaching practices of the participants (9,13,17,18,21,26,28,30,45). Another frequently preferred data collection tool by the researchers was questionnaires.…”
Section: The General Methodological Features Of Pck Studies In the Fimentioning
confidence: 99%
See 1 more Smart Citation
“…Students Knowledge; is defined as determination of pre-details, difficulties on understanding, the misconceptions and causes of misconceptions in relation with subjects that students will learn by teachers or candidate teachers Shulman (1987). The studies on Student Knowledge Components informs us on difficulties of understanding, mistakes and misconceptions, teacher's attıtudes to students about subjects, workıng on it (Grossman, 1990;Fennema and Franke, 1992;Schoenfeld, 1998;Magnusson at al., 1999;An, Kulm and Wu, 2004;Ball at al., 2008;Park and Oliver, 2008;Hacıömeroglu, 2005;Baştürk, 2009;Yeşildere and Akkoç, 2012). As in other areas of mathematics, students have difficulties in learning algebraic issues, both in domestic and foreign studies (Asquith, Stephens, Knuth and Alibali, 2007;MacGregor and Stacey, 1997;Kaya, Keşan, İzgiol and Erkuş, 2016;Livneh and Linchevski, 1999).…”
Section: Extended Summarymentioning
confidence: 99%
“…Öğrenci bilgisi bileşenine yönelik yapılan çalışmalar, üzerinde çalışılan konu ile ilgili olarak, öğrencilerin konuyla alakalı karşılaştıkları anlama güçlükleri, hata ve kavram yanılgıları ve öğretmenlerin öğrencilere karşı tutumlarının neler olduğu hakkında bilgiler vermektedir (An, Kulm ve Wu, 2004;Ball vd., 2008;Baştürk, 2009;Fennema ve Franke, 1992;Grossman, 1990;Hacıömeroglu, 2005;Magnusson vd., 1999;Park ve Oliver, 2008;Schoenfeld, 1998;Yeşildere ve Akkoç, 2012). Türkiye'de öğretmenlerin pedagojik alanbilgileri üzerine yapılan çalışmalar alan yazında son yıllarda yer bulmaktadır (Aksu ve Konyalıoğlu, 2015;Baştürk ve Dönmez, 2011;Eroğlu, 2012, Gökbulut, 2010Gökkurt ve Soylu, 2016, Karahasan, 2010Kutluk, 2011;Şimşek ve Boz, 2015).…”
Section: Introductionunclassified